Precise position measurement of an atom using superposition of two standing wave fields. (22nd February 2017) - Idrees, M; Bacha, B A; Javed, M; Ullah, S A
Abstract: We present a scheme that provides a strong basis for precise localization of atoms, using superposition of two standing wave fields in a three level Λ -type gain assisted model. We show how atomic interference and diffraction occur at a particular node or antinode region of the standing wave fields. Two, three, four and even single localized peaks of atoms are observed in both full-wavelength and sub-half-wavelength domains, with 100 percent localization probability in a single peak. Dark lines appearing in the node region of the standing wave fields show strong evidence for atomic destructive interference. The proposed scheme allows for efficient localization of an atom to a particular point.